2022
DOI: 10.1177/01902725221128392
|View full text |Cite
|
Sign up to set email alerts
|

Facing Others’ Trauma: A Role-Taking Theory of Burnout

Abstract: The experience of “burnout” is characterized by emotional fatigue and detachment associated with intensive stress. Burnout is prevalent across personal and professional spheres, with increasing cultural salience. Multiple factors can contribute to burnout. Here, we focus on one: exposure to others’ trauma. This circumstance spans domains from social service professions to social media newsfeeds, with potentially deleterious effects on the self. To understand the conditions under which trauma exposure results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 82 publications
(139 reference statements)
0
5
0
Order By: Relevance
“…This discomfort was somewhat explained by reduced clarity of the Black couple's intentions which may stem from reduced levels of role‐taking with Black Snapchat characters. Prior scholarship has found that holding stereotypic beliefs reduced both cognitive and empathic role‐taking with victims of intimate partner violence (Groggel, Davis, and Love 2022). A similar mechanism could be occurring here with participants' reliance on racialized stereotypes reducing the extent to which participants actively sought to understand the Black characters' thoughts and feelings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This discomfort was somewhat explained by reduced clarity of the Black couple's intentions which may stem from reduced levels of role‐taking with Black Snapchat characters. Prior scholarship has found that holding stereotypic beliefs reduced both cognitive and empathic role‐taking with victims of intimate partner violence (Groggel, Davis, and Love 2022). A similar mechanism could be occurring here with participants' reliance on racialized stereotypes reducing the extent to which participants actively sought to understand the Black characters' thoughts and feelings.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the findings were conservative and likely underestimated the predictive power of role‐taking on the clarity of characters' intentions or comfort with a flirtatious message. Future work could operationalize empathic role‐taking by comparing participants' self‐reported emotional states prior to and immediately after reading the conversation and incorporate a narrative transportation scale to measure cognitive role‐taking (Groggel, Davis, and Love 2022).…”
Section: Limitationsmentioning
confidence: 99%
“…It is defined by a significant loss of physical and mental energy (de Vries & Bakker, 2022;Schaufeli et al, 2020). The term "burnout" was initially introduced in the 1970s to experience emotional exhaustion, a sense of reduced personal accomplishment, and a loss of motivation in their work (Freudenberger, 1974;Groggel et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent scholarship has cast feeling transportation into a narrative as role‐taking (Groggel et al., 2022). Mead (1934) viewed “taking the attitude of the other” as placing oneself in the other's shoes, anticipating the behavior or state of mind of the other and responding accordingly.…”
Section: Literature Reviewmentioning
confidence: 99%